Chronic hepatitis C treatment outcomes in low- and middle-income countries: a systematic review and meta-analysis - Nathan Ford; Catherine Kirby; Kasha Singh; Edward J Mills; Graham Cooke; Adeeba Kamarulzaman; Philipp duCros (The World Health Organization, 2012)
OBJECTIVE: To assess the effectiveness of treatment for hepatitis C virus (HCV) infection in low- and middle-income countries and identify factors associated with successful outcomes. METHODS: We performed a systematic review and meta-analysis of studies of HCV treatment programmes in low- and middle-income countries. The primary outcome was a sustained virological response (SVR). Factors associated with treatment outcomes were identified by random-effects meta-regression analysis. FINDINGS: The analysis involved data on 12 213 patients included in 93 studies from 17 countries. The overall SVR rate was 52% (95% confidence interval, CI: 48-56). For studies in which patients were predominantly infected with genotype 1 or 4 HCV, the pooled SVR rate was 49% (95% CI: 43-55). This was significantly lower than the rate of 59% (95% CI: 54-64) found in studies in which patients were predominantly infected with other genotypes (P = 0.012). Factors associated with successful outcomes included treatment with pegylated interferon and ribavirin, infection with an HCV genotype other than genotype 1 or 4 and the absence of liver damage or human immunodeficiency virus infection at baseline. No significant difference in the SVR rate was observed between weight-adjusted and fixed-dose ribavirin treatment. Overall, 17% (95% CI: 13-23) of adverse events resulted in treatment interruption or dose modification, but only 4% (95% CI: 3-5) resulted in treatment discontinuation. CONCLUSION: The outcomes of treatment for HCV infection in low- and middle-income countries were similar to those reported in high-income countries.